2000
DOI: 10.1029/1999jb900343
|View full text |Cite
|
Sign up to set email alerts
|

Particle recycling and oscillations of volcanic eruption columns

Abstract: Abstract. We study the dynamics of sedimentation and reentrainment of particles from the umbrella cloud above an axisymmetric, turbulent, particle-laden buoyant plume. We develop a model to show that the reentrainment of particulate material into the uprising plume will cause the particle flux to increase by a factor of e between the plume source and the umbrella cloud. A buoyant plume rising in an environment of uniform density may thereby become negatively buoyant if its particle loading becomes suf[iciently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 31 publications
(27 reference statements)
1
56
0
Order By: Relevance
“…For a given mass flux, the increase in the critical velocity may be as large as 5%, so that the fluctuations reported are most significant near the source. Veitch and Woods (2000) showed that, for an incompressible laboratory scale plume, the fractional increase in particle increase from source to top is e≈2.71. However, for a compressible plume, this result is modified (see the section Fallout) because the total solid mass flux entrained decreases.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…For a given mass flux, the increase in the critical velocity may be as large as 5%, so that the fluctuations reported are most significant near the source. Veitch and Woods (2000) showed that, for an incompressible laboratory scale plume, the fractional increase in particle increase from source to top is e≈2.71. However, for a compressible plume, this result is modified (see the section Fallout) because the total solid mass flux entrained decreases.…”
Section: Resultsmentioning
confidence: 98%
“…However, as the mass flux reaches Q CE at time t 1 , we move into a regime where the plume can not remain stable because of the reentrainment of particles (cf. the experiments of Veitch and Woods, 2000). If the rate of increase of the mass flux is sufficiently slow then the eruption column may fluctuate between plume-forming and flow-forming behaviour.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations